Postoperative hypoparathyroidism – what the family doctor should know - Nowicka-Stążka, Patrycja; Malicka, Joanna Elżbieta; Tarach, Jerzy S. (Family Medicine & Primary Care Review, 2017)
Background . Hypoparathyroidism is a condition of parathyroid hormone (PTH ) deficiency, which can be inherited, but it is also encountered mainly after thyroid or parathyroid gland surgery. PTH stimulates calcium reabsorption in the kidneys and calcium release from the bones. It also stimulates renal production of 1,25-dihydroxyvitamin D (calcitriol) from 25-hydroxyvitamin D. Hypocalcaemia caused by PTH deficiency can lead to cramping and twitching of the muscles or tetany and many other symptoms. Objectives . The aim of the study was to retrospectively evaluate, in own material, the prevalence and clinical picture of hypoparathyroidism, caused by various surgical procedures performed on the thyroid gland. Material and methods. The study group involved 145 patients after thyroid surgery, treated for various reasons in the Department of Endocrinology of the Medical University in Lublin in the years 2000–2017. The authors analyzed the medical histories and clinical pictures of the patients and the results of laboratory tests, including calcium, phosphorus and PTH concentrations. Results. 32 patients were diagnosed with hypoparathyroidism, and 113 patients without calcium concentration disorders. The analyzed groups did not differ significantly in respect to gender, age and indications for thyroid surgery. We found no correlation between the length of follow up and PTH concentration, a weak negative correlation with total calcium concentration and a quite strong negative correlation with ionized calcium concentration in the subgroup with newly diagnosed hypoparathyroidism. Conclusions . The clinical picture of hypocalcaemia varies, and it is important to take into account the possibility of hypoparathyroidism in a patient after thyroid surgery.